Therapeutic Effect of Cu(II) Complex with Photocatalytic Property on Gastric Cancer by Inhibiting the Proliferation of Tumor Cells - Dan Yu; Shuqin Li (Journal of Chemistry)
In situ hydrolysis of 1,4,5,8-naphthalenetetracarboxylic dianhydride (L) and simultaneous self-assembly with Cu(II) ions afforded a new Cu(II) compound formulated as [Cu(L) (4,4′-bpy)0.5(H2O)]n (1), which is structurally determined by a series of characterization techniques, such as powder X-ray diffraction (PXRD), thermogravimetric Analysis (TGA), and elemental analysis. It is noteworthy that compound 1 can catalyze the degradation of methylene blue (MB) in aqueous solution under UV irradiation. This paper also investigated and evaluated its application value and research mechanism in gastric cancer. However, we also used real-time reverse transcription-polymerase chain reaction (RT-PCR) to detect the activation of vascular endothelial growth factor (VEGF) signaling pathway, and Cell Counting Kit-8 (CCK-8) method was used to calculate the inhibition activity of 1 on gastric cancer cell viability.